Pediatric Cancer Parents' Salivary Alpha-Amylase (sAA) Level - Utami, Kadek Cahya; Januraga, Pande Putu; Lesmana, Cokorda Bagus Jaya; Ani, Luh Seri (Babali Nursing Research, 2024)
Introduction: Parenting a child with cancer presents significant challenges that can increase parental stress. Without appropriate interventions, this stress may impair parents' ability to provide the best possible care for their children. To implement effective care strategies, healthcare professionals, particularly nurses, must assess the stress levels experienced by parents. One objective indicator of stress is salivary Alpha-Amylase (sAA), which can be measured using a cocorometer through saliva samples. This study aimed to assess sAA levels among parents of children with cancer. Methods: The research employed a descriptive, quantitative, cross-sectional design with a sample of 30 parents from Rumah Singgah Yayasan Peduli Kanker Anak Bali, selected through purposive sampling. The research instrument used was a NIPRO-brand cocorometer. Results: Findings revealed an average sAA level of 34.93 kIU/L, with a range from 5 kIU/L to 60 kIU/L. Higher sAA levels were observed among female respondents, those residing outside of Bali, and those caring for children under two years old. Conclusion: Continuous monitoring of parental stress using objective measures such as sAA is recommended for nurses to support optimal stress management.